CAN PEOPLE BE CONTROLLED BY MEDIA AND SOCIAL MEDIA LIKE DRONES? ARE THERE "IDRONES"? - Doepp, Manfred (International Journal of Engineering Science Technologies, 2025)
Drones are already determining the course of wars today, as they are inexpensive and perfectly controllable, especially when combined with satellite surveillance and AI. Something similar is happening in computer games, which have been perfected in that the characters appear to act autonomously. In social media, influencers can control and direct their followers so that their individuality is lost. The programming rules are largely identical. Cultural pessimists fear that this will lead to the end of freedom of opinion and behavior and that a surveillance state could be established. The tendencies in this direction are serious and can be found openly on the Internet. People like "iDrones": this can still be prevented.